Improving rotavirus vaccine coverage: Can newer-generation and locally produced vaccines help? - Jacqueline Deen; Anna Lena Lopez; Suman Kanungo; Xuan-Yi Wang; Dang Duc Anh; Milagritos Tapia; Rebecca F. Grais (Taylor & Francis Group, 2018)
There are two internationally available WHO-prequalified oral rotavirus vaccines (Rotarix and RotaTeq), two rotavirus vaccines licensed in India (Rotavac and Rotasiil), one in China (Lanzhou lamb rotavirus vaccine) and one in Vietnam (Rotavin-M1), and several candidates in development. Rotavirus vaccination has been rolled out in Latin American countries and is beginning to be deployed in sub-Saharan African countries but middle- and low-income Asian countries have lagged behind in rotavirus vaccine introduction. We provide a mini-review of the leading newer-generation rotavirus vaccines and compare them with Rotarix and RotaTeq. We discuss how the development and future availability of newer-generation rotavirus vaccines that address the programmatic needs of poorer countries may help scale-up rotavirus vaccination where it is needed.